Designing and Implementing an Elementary Science After School Field Experience - Cartwright, Tina (Innovations in Science Teacher Education, 2016)
Field experiences provide an important opportunity for preservice teachers to observe and practice science instruction. Too often, insufficient time is allotted for elementary science instruction in the formal classroom. This paper outlines the opportunities and lessons learned from an after school field experience where preservice elementary teachers worked in two-person teams with a classroom mentor teacher at local elementary schools and community centers to deliver two science lessons per week during an elementary science methods course. Multiple evidences of success are presented at the student and also at the preservice teacher levels. And finally, the important lessons learned include the characteristics of the after-school site, the “instructional” setting, the availability and storage of materials, the co-teacher preservice teams, and the presence and training of the mentor teacher.